COMPARISON OF TOPICAL AND INTRAVENOUS LIGNOCAINE IN PATIENTS UNDERGOING LARYNGEAL MASK AIRWAY INSERTION UNDER PROPOFOL: A RANDOMIZED CONTROLLED TRIAL - SULTAN, A; ALI, A; ALSAADI, EHH; MAAN, MAM; NASEEM, R; HUSSAIN, S (Biological and Clinical Sciences Research Journal, 2024)
Laryngeal mask airway (LMA) insertion is a common technique used in general anesthesia, but it may induce airway reflexes such as coughing, gagging, and laryngospasm. Lignocaine, whether administered topically or intravenously, is often used to suppress these reflexes. However, the comparative efficacy of these two routes remains unclear. Objective: This study aims to compare the effectiveness of topical versus intravenous lignocaine in facilitating LMA insertion and minimizing airway complications in patients undergoing propofol anesthesia. Methods: A randomized controlled trial was conducted on 62 patients undergoing elective surgeries under general anesthesia at a tertiary care hospital. Patients were randomly assigned into two groups: Group A (n = 31) received 40 mg of topical lignocaine aerosol, while Group B (n = 31) received intravenous lignocaine 1.5 mg/kg. Both groups were induced with propofol (2 mg/kg) prior to LMA insertion. Primary outcomes included the number of LMA insertion attempts, airway responses (coughing, gagging, laryngospasm), and hemodynamic parameters (systolic blood pressure, diastolic blood pressure, and heart rate) recorded at baseline and 1, 2, and 3 minutes post-insertion. Results: LMA insertion on the first attempt was successful in 93.5% of patients in the topical lignocaine group compared to 74.2% in the intravenous group (p = 0.03). Airway reflexes were significantly lower in the topical group, with coughing, gagging, and laryngospasm rates of 6.5%, 16.1%, and 9.7%, respectively, compared to 32.3%, 45.2%, and 29.0% in the intravenous group (p < 0.05). Hemodynamic parameters, including systolic and diastolic blood pressure and heart rate, showed no significant differences between the two groups at baseline or post-insertion. Conclusion: Topical lignocaine significantly improves conditions for LMA insertion compared to intravenous lignocaine, resulting in fewer airway complications while maintaining similar hemodynamic stability. Therefore, topical lignocaine is recommended for optimizing LMA insertion during propofol anesthesia.